Business transformation : a roadmap for maximizing organizational insights - Zeid, Aiman (Wiley and SAS business series., 2014)
"Effectively introduce and promote analytics within your enterprise. All companies use information to set strategies and accomplish business objectives. But how many CEOs and CIOs would say they are satisfied that their companies get maximum value from information? The Data Advantage reveals how SAS's Information Evolution Model (IEM) can be used together with analytics for groundbreaking results. Author Aiman Zeid provides the necessary information you need to introduce and promote the use of analytics and insight across your organization. Along with examples and best practices of global companies that have successfully been through this process, you'll learn how to identify the starting point and develop a road map for execution. Reveals how to introduce and promote the use of analytics and insights across your organization Written by a lead developer at SAS global Business Intelligence Competency Center program and services Features global case studies and examples Practical and insightful, this reference provides businesses with an essential blueprint for creating improvements that optimize business returns and put the potential of data analytics to work"--